(untitled) (Biological Sciences - PJSIR, 2022)
Effects oflodging and nitrogen rate were studied in a field trial of oilseed rape Brassicanapus L. Lodging decreased seed yield (16%) compared with a frame-raised crop. The yield decreased because of a significant reduction of each of the yield components coupled with a reduced plant population caused by stem breakage at the ground level. Lodging also reduced the final crop dry weight and harvest index. Seed yield also decreased from the 400 kg ha’ of nitrogen application compared with 200 kg ha’. A general decrease in pod number m", seed number pod" and seed weight caused lower yields. The use of 400 kg ha -I of nitrogen changed the contribution of terminal raceme and individual branches with respect to seed yield. Seed nitrogen content and nitrogen yield increased at the 400 kg ha’, lowering both seed oil content and oil yield.